Defining the in Vivo Role for Cytochrome b(5) in Cytochrome P450 Function through the Conditional Hepatic Deletion of Microsomal Cytochrome b(5) - Finn, Robert D. (American Society for Biochemistry and Molecular Biology, 2008)
In vitro, cytochrome b(5) modulates the rate of cytochrome P450-dependent mono-oxygenation reactions. However, the role of this enzyme in determining drug pharmacokinetics in vivo and the consequential effects on drug absorption distribution, metabolism, excretion, and toxicity are unclear. In order to resolve this issue, we have carried out the conditional deletion of microsomal cytochrome b(5) in the liver to create the hepatic microsomal cytochrome b(5) null mouse. These mice develop and breed normally and have no overt phenotype. In vitro studies using a range of substrates for different P450 enzymes showed that in hepatic microsomal cytochrome b(5) null NADH-mediated metabolism was essentially abolished for most substrates, and the NADPH-dependent metabolism of many substrates was reduced by 50–90%. This reduction in metabolism was also reflected in the in vivo elimination profiles of several drugs, including midazolam, metoprolol, and tolbutamide. In the case of chlorzoxazone, elimination was essentially unchanged. For some drugs, the pharmacokinetics were also markedly altered; for example, when administered orally, the maximum plasma concentration for midazolam was increased by 2.5-fold, and the clearance decreased by 3.6-fold in hepatic microsomal cytochrome b(5) null mice. These data indicate that microsomal cytochrome b(5) can play a major role in the in vivo metabolism of certain drugs and chemicals but in a P450- and substrate-dependent manner.